Orthokeratology Lens Wear for 2 Years in Children Did Not Alter Tear Film Lipid Thickness by Non-Invasive Interferometry - Yu, Haozhe; Yuan, Yifei; Wu, Wenyu; Zeng, Weizhen; Tong, Louis; Zhang, Yu; Feng, Yun (Frontiers in Medicine, 2022)
Purpose: Previous studies suggest that overnight orthokeratology (OOK) may be detrimental for tear function. We aimed to investigate the effect of OOK on lipid layer thickness (LLT), blink pattern as well as meibomian gland and elucidate the relationship of these variables. Methods: Thirty-seven participants who wore orthokeratology (OOK) lenses every night for at least 2-years, and twenty-four healthy non-contact lens wearers (controls) were enrolled in this retrospective study. LipiView interferometry, blink pattern analysis, the ocular surface status as well as morphology and function of meibomian gland were determined. Results: The OOK group and healthy controls had similar LLT, blink patterns, the ocular surface status and the function of meibomian gland. OOK participants demonstrated higher meiboscore in the lower eyelids (P < 0.05) but not in upper eyelids. Within the OOK group, LLT was significantly impacted by the partial blink rate (P < 0.05) and the total score of upper meibomian gland (P = 0.10). Conclusions: Wearing OOK for two or more years increased lower eyelid meibomian gland dropout but did not have reduction of LLT.